Criminal Law Policy Analysis Concerning Decriminalization of Abortion - Dewic Sri Ratnaning Dhumillah; Aktuaris Harefa (Transpublika Publisher, 2025)
Pregnancy due to rape is a pregnancy that occurs outside of a person's will. When the victim is faced with violence or threats of violence, the victim is forced to have sex with the perpetrator outside of marriage. Therefore, that unwanted pregnancies generally result in abortion. In Indonesia, the incidence of unwanted pregnancies reaches 121 million per year. This figure shows that there are 64 unwanted pregnancies occurring in every 1,000 women aged 15-49 years and it is recorded that 73.3 million abortions occur each year, which is equivalent to 39 abortions per 1,000 women each year. Normatively, abortion is regulated by Health Law No. 17 of 2023, Article 60, which prohibits everyone from having an abortion except for the criteria permitted by national criminal law. This study seeks to analyzes Indonesia’s criminal law policy on abortion decriminalization and legal gaps for rape victims over 14 weeks gestation, using a normative juridical approach to examine relevant laws and their alignment with state policy. The decriminalization of abortion through the 2023 national criminal code is a criminal law policy that is harmonized from the previous law and abortions carried out based on the new national criminal law policy have a tendency to be victim-oriented. Although abortion has been decriminalized, the government has yet to establish clear policies, systems, and legal protections for rape victims with pregnancies over 14 weeks.